Immunoassay of P2 protein in cerebrospinal fluid in neurological disorders. - Colover, J (1991)
Cerebrospinal fluid samples were obtained at lumbar puncture from 53 patients with a wide variety of neurological disorders. Cerebrospinal fluid samples were tested for the presence of P2 protein, a constituent of myelin, with an enzyme linked immunosorbent assay technique using a specific polyclonal antibody. High concentrations of P2 in the cerebrospinal fluid paralleled a raised IgG index (clearance ratio), the presence of oligoclonal bands, as well as raised white cell counts or depressed albumin:IgG ratios. Twenty one patients had been diagnosed as having definite or probable multiple sclerosis and the remaining 32 had other conditions. Of the 13 patients with high positive P2, 12 (92%) were in the multiple sclerosis category; of the 40 patients with low (12) or undetectable (28) P2 concentrations, only nine (23%) were diagnosed as having multiple sclerosis. In this patient population the presence of high immunoreactive P2 concentrations in cerebrospinal fluid was closely associated with evidence of intrathecal immunoglobulin synthesis and with the clinical diagnosis of multiple sclerosis. On this basis it is suggested that immunoassay of P2 concentration in the cerebrospinal fluid may be of potential value in the investigation of patients with demyelinating disorders.